Selectivity of registered pesticides for the corn crop on immature stages of Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) - Tatiele Pereira dos Santos; Claubert Wagner Guimarães de Menezes; Carlos Henrique Batista; Eliane Souza Gomes Brito; Wagner de Souza Tavares; José Cola Zanuncio (Ciência e Agrotecnologia, 2020)
ABSTRACT Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae) is an egg parasitoid of lepidopteran pests in corn, Zea mays L. (Poaceae), in Brazil. Chemical products used in agriculture can be toxic to this biocontrol agent. The objective of the present study was to evaluate the longevity, parasitism and emergence of T. pretiosum parasitizing Mediterranean flour moth, Anagasta kuehniella Zeller, 1879 (Lepidoptera: Pyralidae), eggs treated with herbicide solutions with the active ingredients (chemical group) atrazine (triazines), paraquat dichloride (bipyridylium) and nicosulfuron (sulfonylurea). Pure distilled water was used as a negative control, and a solution of a product with λ-cyhalothrin + thiamethoxam (pyrethroid + neonicotinoid, respectively) was used as the positive control. The experimental design was completely randomized, with five treatments and 10 replicates. Anagasta kuehniella eggs were stored for two periods after treatment, 24 and 48 hours. These eggs were subjected to parasitism for two subjecting periods, 24 and 48 hours. The results were analysed statistically and classified according to the International Organization for Biological Control (IOBC). Atrazine and nicosulfuron reduced the longevity of T. pretiosum females. Nicosulfuron and the combination λ-cyhalothrin + thiamethoxam reduced the parasitism and emergence of this natural enemy. The paraquat dichloride-based herbicide was the least toxic and therefore represents a potential option for controlling weeds with low toxicity to the T. pretiosum parasitoid.